Analysis Of Support Management In Drug Management In The Pharmaceutical Installation Of Permata Serdang Hospital - Paramitha, Nadya Cahya; Oktamianti, Puput (Sean Institute, 2024)
Support management in the Pharmaceutical Installation has the aim of supporting the drug management system so that drug management in hospital agencies runs optimally. Pharmaceutical support management consists of human capital, organizational capital, information capital and finance capital, the four of which are interrelated so as to make the system that has been running effective and efficient. The purpose of this study was to determine the condition of support management at the Permata Serdang Hospital Pharmacy Installation. This research is a qualitative research with a case study approach and data collected from interviews and secondary data from the review of hospital documents. The results of interviews with informants from the Pharmacy Installation of Permata Serdang Hospital show that from the human capital aspect there are still problems related to the lack of human resources in related units. In organizational capital, it is known that an organizational structure has been formed that supports a work culture that focuses on patient safety and service efficiency. In information capital, the use of SIMRS has been utilized to support the management of medicines and services, although there are still some technical problems such as slow application and has not been fully utilized for decision making in the management of medicines. There is no information obtained from the finance department for the finance capital aspect, but the Hospital Pharmacy Installation carries out a control process to prevent losses from medicines that have been purchased. Therefore, the Hospital needs to improve the quality of management support such as increasing the number of human resources who also support the organization in the Permata Serdang Hospital Pharmacy Installation, as well as maximizing the function of SIMRS as a decision-making tool in the hope that drug management will run more effectively and efficiently.